Предмет: Математика,
автор: hgffffgkhgmailcom
{2(x + y) – x + 6 = 0,
{3x - (x - y) = 0;
Ответы
Автор ответа:
3
Пошаговое объяснение:
раскрываем скобки
2х+2у-х+6=0
3х-х+у=0
х-2у=-6
2х+у=0
х+2*2х=-6
у=-2х
5х=-6
у=-2х
х=-6/5
у=-2*(-6/5)
х=-6/5
у=12/5
pdddanil228:
ответ должен быть 2 и -4
Похожие вопросы
Предмет: Русский язык,
автор: anna77s
Предмет: Русский язык,
автор: zahar0401
Предмет: Русский язык,
автор: ghfrficdjrfujcv
Предмет: Музыка,
автор: khudyashovav
Предмет: Физика,
автор: Андрюша11111111